Integrally injection-molded nanocrystalline strip winding iron core and preparation method thereof

After annealing and crystallization and stress removal of the nanocrystalline strip, it is wound into a closed magnetic circuit and impregnated and solidified. Combined with an integrated injection molding process, the problem of insufficient tightness and uniformity of the nanocrystalline strip core is solved. Significantly improves magnetic permeability and stress deformation resistance.

CN119446703AActive Publication Date: 2025-02-14SHENZHEN YN TECH CO LTD

Patent Information

Application Number
CN202510027936.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-14
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

After the existing nanocrystalline strip core is formed, the compactness and uniformity of the magnetic core are insufficient, the stress deformation resistance is low, and it is difficult to be suitable for the integrated injection molding process, which is prone to cracking and air gaps to affect the magnetic permeability of the magnetic core. .

Method used

The amorphous nanocrystalline strip material after annealing crystallization and stress removal treatment is wound into a closed magnetic circuit, and is immersed in the adhesive resin solution and heated and cured to form a magnetic core, and then placed in a hard shell and inserted into the copper bar. The plastic parts between the magnetic core and the copper row are completed by injection molding, and integrated injection molding is achieved.

Benefits of technology

The core's resistance to high temperature and high pressure stress deformation performance is improved, the bonding force between the core and the copper row is enhanced, cracking and air gaps are reduced, and magnetic permeability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446703A_ABST
    Figure CN119446703A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of soft magnetic materials, and particularly relates to an integrally injection-molded nanocrystalline strip winding iron core and a preparation method thereof. The preparation method comprises the following steps: performing annealing crystallization and destressing treatment on an amorphous nanocrystalline strip, winding the amorphous nanocrystalline strip into a closed magnetic circuit, then immersing the closed magnetic circuit into an adhesive resin glue solution, taking out the closed magnetic circuit, and heating, curing and forming the closed magnetic circuit to obtain a magnetic core; the obtained magnetic core is placed in a hard shell, then a copper bar is inserted, finally, a plastic part between the magnetic core and the copper bar is completed through injection molding, and the nanocrystalline strip winding iron core integrally formed through injection molding is obtained. According to the method, integrated injection molding of the magnetic core, the copper bar and the plastic part can be achieved. By further optimizing an adhesive resin glue solution system formed by curing, the curing effect and the magnetic performance of the iron core can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to an integrally injection-molded nanocrystalline strip winding core and a preparation method thereof. Background Art

[0002] As the integration of power modules in the field of new energy vehicles becomes higher and higher, the volume requirements of various components are becoming more and more extreme. Traditional filter circuits usually first complete the injection molding of the connecting copper bars and plastic parts in the circuit, and then assemble them with the magnetic core with a protective box, or place the magnetic core without a protective box in the shell of the injection molded part and fix it with glue to complete the assembly. This structure is large in size and requires more assembly work.

[0003] The preparation method of the existing nanocrystalline strip iron core is generally to prepare the strip into a closed magnetic circuit by winding, and then to complete it by dipping and curing. For example, the Chinese invention patent application document with the publication number CN114927303A discloses a nanocrystalline magnetic core, in which the straight strip after thermal stress treatment is wound into a ring magnetic core by an automatic winding machine, and then subjected to nanocrystallization heat treatment and magnetic field heat treatment, and finally packed into a plastic protective box, thereby obtaining a high magnetic induction nanocrystalline inductor magnetic core. However, the nanocrystalline strip has the defects of being fragile and poor in flexibility. Although the deformation and cracks can be reduced to a certain extent by pre-stress relief treatment, the compactness and uniformity of the magnetic core formed by winding still need to be further improved. The stress deformation resistance after dipping and curing is low, and it is difficult to be applied to the pressure in the one-piece injection molding process, and it is easy to produce cracks and air gaps that affect the magnetic permeability of the magnetic core. Summary of the invention

[0004] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing an integrally injection-molded nanocrystalline ribbon wound core.

[0005] Another object of the present invention is to provide a nanocrystalline ribbon wound core prepared by the above method.

[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing an integrally injection-molded nanocrystalline ribbon wound core comprises the following preparation steps: (1) The amorphous nanocrystalline strip is annealed, crystallized and stress-relieved and wound into a closed magnetic circuit, then immersed in an adhesive resin solution, taken out and heated and cured to obtain a magnetic core; (2) The magnetic core obtained in step (1) is placed in a hard shell, and then the copper busbar is inserted. Finally, the plastic part between the magnetic core and the copper busbar is completed by injection molding to obtain an integrally injection-molded nanocrystalline ribbon wound iron core.

[0007] Furthermore, the amorphous nanocrystalline ribbon described in step (1) has a thickness of 10-30 μm and a composition system of FeSiB, FeSiBC, FeNiSiB, FeCuNbSiB, FeNiCuNbSiB, FeCoCuNbSiB, FeCuMoSiB, FeNiCuMoSiB, FeCoCuMoSiB, FeCuPCSiB, FeNiCuPCSiB, and FeCoCuPCSiB.

[0008] Furthermore, the specific steps of annealing, crystallization and stress relief treatment and winding into a closed magnetic circuit in step (1) are as follows: the amorphous nanocrystalline strip is firstly wound into a closed magnetic circuit, and then isothermal magnetic field annealing, crystallization and stress relief treatment are performed under the conditions of 400-650°C temperature and magnetic field.

[0009] Furthermore, the specific steps of annealing, crystallization, stress relief treatment and winding into a closed magnetic circuit in step (1) are as follows: The amorphous nanocrystalline strip is added into the roll-to-roll annealing device and conveyed by the pressure rollers. At the same time, a linear laser heating device, an electromagnetic induction heating device or a Joule heat treatment device is arranged along the width direction of the strip on one or both sides of the strip. Linear dynamic crystallization annealing and stress relief treatment are performed during the conveying process of the strip, and then the strip is wound into a closed magnetic circuit.

[0010] Furthermore, the laser heating device is a laser with a power of 50~2000W. The high-energy laser beam emitted by the laser performs line scanning along the width direction of the strip, and the strip in the area where the laser beam flows out of the beam rapidly undergoes nanocrystallization and stress relief annealing. The electromagnetic induction heating device is a flat induction heating coil with a power of 50~10000W. The strip in the area of ​​the induction heating coil rapidly undergoes nanocrystallization and stress relief annealing. The Joule heat treatment device is a pair of carbon brush electrodes arranged on both sides of the strip in the width direction, and the carbon brush electrodes are output by a DC power supply with a current intensity of 1~200A. The area where the current flows completes the rapid nanocrystallization and stress relief annealing of the strip.

[0011] The above-mentioned local linear dynamic heat treatment process can improve the controllability of the crystallization process, effectively reduce the crystallization exothermic aggregation, and thus effectively improve the soft magnetic properties of the material.

[0012] Furthermore, the closed magnetic circuit in step (1) is annular, rectangular or racetrack-shaped.

[0013] Furthermore, the adhesive resin glue in step (1) is epoxy resin glue, polyurethane resin glue, polyacrylate resin glue or silicone resin glue. More preferably, it is silicone resin glue. Compared with epoxy resin and other glues, the silicone resin glue used in the present invention has better high temperature resistance and flexibility, and the magnetic core after dipping and curing has better resistance to high temperature and high pressure stress deformation.

[0014] Furthermore, the epoxy resin glue includes an epoxy resin matrix and an epoxy resin curing agent, and the epoxy resin curing agent is one of amino resin, ethylenediamine, m-phenylenediamine, maleic anhydride, and dicyandiamide; the polyacrylate resin glue includes a polyacrylate resin matrix and a polyacrylate curing agent, and the polyacrylate curing agent is one of isocyanate, aziridine, and triacetylacetonate aluminum; the silicone resin glue includes vinyl polysiloxane and hydrogen-containing polysiloxane, or the silicone resin glue includes epoxy polysiloxane and amino polysiloxane.

[0015] Further preferably, the epoxy polysiloxane is prepared by the following method: The hydrogen-containing silicone oil, allyl glycidyl ether and an organic solvent are mixed evenly, and then a chloroplatinic acid isopropanol solution catalyst is added and heated for reaction to obtain epoxy polysiloxane.

[0016] Preferably, the number average molecular weight of the hydrogen-containing silicone oil is 1000-10000, and the hydrogen content is 0.2-1wt.%; the amount of allyl glycidyl ether is 5%-30% of the mass of the hydrogen-containing silicone oil; the organic solvent is one or more of N,N-dimethylformamide, toluene, xylene, ethyl acetate, butyl acetate, n-hexane, n-heptane, acetone, butanone, tetrahydrofuran, and isopropanol; the amount of the organic solvent is 5%-20% of the total mass of the hydrogen-containing silicone oil and allyl glycidyl ether; the temperature of the heating reaction is 70-90°C, and the time is 1-6h.

[0017] More preferably, the amino polysiloxane has an amino group content of 0.2% to 2% by mass and a viscosity of 50 to 1000 cps.

[0018] The present invention adopts the curing adhesive system of the above-mentioned epoxy polysiloxane and amino polysiloxane. Compared with the curing adhesive system of vinyl polysiloxane and hydrogen-containing polysiloxane, it has better adsorption and adhesion to nanocrystalline strips, can better penetrate into the gaps between the layers of the wound strip and achieve higher bonding strength, thereby achieving better bonding and curing effect and stress deformation resistance.

[0019] Furthermore, the temperature of the heating and curing molding in step (1) is 60~220°C.

[0020] Furthermore, the injection molding temperature in step (2) is 120-360° C. and the pressure is 30-300 MPa.

[0021] Furthermore, the material of the hard shell in step (2) is aluminum alloy, iron alloy or plastic.

[0022] A nanocrystalline strip wound iron core is prepared by the method.

[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) The magnetic core of the present invention is obtained by using nanocrystalline strips after annealing, crystallization and stress relief treatment and then being cured by resin dipping. It can better resist the high temperature and high pressure stress deformation during the injection molding process, so that it can be integrally injection molded with the copper busbar and the plastic parts.

[0024] (2) The present invention can significantly improve the curing effect and the magnetic properties of the iron core by further optimizing the adhesive resin liquid system used for curing. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the structure of the nanocrystalline ribbon wound core obtained in Example 1 of the present invention; Figure 2 This is a schematic diagram of a finished product after the magnetic core, plastic parts and copper busbar are integrally injection molded in Example 1 of the present invention; Figure 3 and Figure 4 Schematic diagram of the process of linear dynamic crystallization annealing treatment in Example 2 of the present invention. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Example 1

[0027] A method for preparing an integrally injection-molded nanocrystalline ribbon wound core comprises the following preparation steps: (1) A 18 μm thick, Fe 73.5 Cu1Nb3Si 15.5 The amorphous nanocrystalline ribbon of B7 (at.%) was wound into a racetrack-shaped closed magnetic circuit, then placed in a heating furnace and heated to 560°C and subjected to isothermal magnetic field annealing crystallization and stress relief treatment for 1.5 h in the presence of a magnetic field to obtain a nanocrystalline ribbon magnetic core.

[0028] (2) The nanocrystalline ribbon magnetic core obtained in step (1) is immersed in bisphenol A type liquid epoxy resin glue (using ethylenediamine as a curing agent, commercially available) for 30 minutes, and then taken out and heated to 120° C. in a curing furnace for curing to obtain a magnetic core.

[0029] (3) The magnetic core obtained in step (2) is placed in an aluminum alloy hard shell, and then the copper busbar is inserted. Finally, the plastic part between the magnetic core and the copper busbar is completed by injection molding (injection molding temperature 280°C, pressure 50MPa) to obtain an integrally injection-molded nanocrystalline ribbon wound iron core.

[0030] The schematic diagram of the structure of the nanocrystalline ribbon wound core obtained in this embodiment and the schematic diagram of the finished product after integral injection molding are shown in Figures 1 and 2 respectively. Figure 1 and Figure 2 shown. Example 2

[0031] A method for preparing an integrally injection-molded nanocrystalline ribbon wound core, compared with Example 1, adopts a linear dynamic crystallization annealing and stress relief treatment method to replace isothermal magnetic field annealing crystallization and stress relief treatment, comprising the following preparation steps: (1) A 18 μm thick, Fe 73.5 Cu1Nb3Si 15.5 The amorphous nanocrystalline strip of B7 (at.%) is added to the roll-to-roll annealing device and conveyed by the rollers. The roller conveying speed is 6m / min. At the same time, a linear laser heating device is set along the width direction of the strip on one side of the strip. During the strip conveying process, a high-energy laser beam with a power of 1000W is synchronously turned on to scan along the width direction of the strip. The strip in the area where the laser beam flows out of the beam quickly undergoes nanocrystallization and stress relief annealing. The corresponding processing flow diagram is shown in the figure below. Figure 3 and Figure 4 shown.

[0032] (2) The nanocrystalline ribbon obtained after the treatment in step (1) is wound into a racetrack-shaped closed magnetic circuit, and then immersed in a bisphenol A liquid epoxy resin glue (using ethylenediamine as a curing agent, commercially available) for 30 minutes. After being taken out, it is heated to 120° C. in a curing furnace to be cured and formed to obtain a magnetic core.

[0033] (3) The magnetic core obtained in step (2) is placed in an aluminum alloy hard shell, and then the copper busbar is inserted. Finally, the plastic part between the magnetic core and the copper busbar is completed by injection molding (injection molding temperature 280°C, pressure 50MPa) to obtain an integrally injection-molded nanocrystalline ribbon wound iron core. Example 3

[0034] A method for preparing an integrally injection-molded nanocrystalline ribbon wound core. Compared with Example 1, polyacrylate resin glue (using isocyanate as a curing agent, commercially available) is used instead of epoxy resin glue, the heating curing temperature is 100° C., and the rest is the same. Example 4

[0035] A method for preparing an integrally injection-molded nanocrystalline strip wound core. Compared with Example 1, a silicone resin adhesive (containing a catalytic amount of a platinum complex catalyst and an appropriate amount of an acetylene alcohol stabilizer, commercially available) composed of vinyl polysiloxane (vinyl content 6.2wt%, viscosity 500cps) and hydrogen-containing polysiloxane (hydrogen content 0.5%, viscosity 100cps) in a mass ratio of 2:1 is used to replace the epoxy resin adhesive, and the heating curing temperature is 90°C. The rest is the same. Example 5

[0036] A method for preparing an integrally injection-molded nanocrystalline strip wound core. Compared with Example 1, an organic silicone resin adhesive composed of epoxy polysiloxane (epoxy content 6.2wt%, viscosity 500cps) and amino polysiloxane (amino content 0.5%, viscosity 100cps, commercially available) in a mass ratio of 2:1 is used to replace the epoxy resin adhesive, the heating curing temperature is 100°C, and the rest is the same.

[0037] The epoxy polysiloxane is prepared by the following method: By mass, 100 parts of hydrogen-containing silicone oil with a number average molecular weight of 5600 and a hydrogen content of 0.52wt.%, 20 parts of allyl glycidyl ether and 10 parts of toluene were mixed, and a chloroplatinic acid isopropanol solution catalyst with a platinum content of 50ppm was added under nitrogen protection, heated to 80°C and stirred for reaction for 4 hours to obtain an epoxy polysiloxane with an epoxy content of 6.2wt% and a viscosity of 500cps.

[0038] The relative magnetic permeability (100 kHz) of the wound core obtained in the above embodiment was tested, and the results are shown in Table 1 below.

[0039] Table 1 Test Group Magnetic Permeability Example 1 24560 Example 2 31280 Example 3 26720 Example 4 28450 Example 5 35840 It can be seen from the comparison results of Example 1 and Example 2 in Table 1 that the linear dynamic crystallization annealing process used in the present invention can significantly improve the magnetic permeability compared with the conventional heating furnace overall annealing process. The reason is that the linear dynamic crystallization annealing process can effectively reduce the crystallization exothermic aggregation, improve the controllability of the crystallization process, prevent coarse grains, refine the size of nanocrystals and improve uniformity, thereby effectively improving the magnetic permeability. It can be seen from the comparison results of Examples 4 and 5 with Examples 1 and 3 that the use of silicone resin glue has better high temperature resistance and flexibility than conventional epoxy resins, acrylate resins and other glues, and the magnetic core after dipping and curing has better resistance to high temperature and high pressure injection stress deformation performance. After integral injection molding, it can ensure good structural integrity and uniformity, reduce cracking and air gaps, and thus improve the magnetic permeability. It can be seen from the comparison results of Example 4 and Example 5 that the dipping and curing system composed of epoxy polysiloxane and amino polysiloxane can further significantly improve the magnetic permeability compared with the dipping and curing system of vinyl polysiloxane and hydrogen-containing polysiloxane. The reason is that epoxy polysiloxane and amino polysiloxane have better adhesion and bonding properties to nanocrystalline tapes, can better penetrate into the gaps between the layers of the wound tape and achieve higher bonding strength, thereby achieving better bonding and curing effects and resistance to injection stress deformation.

[0040] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing an integrally injection molded nanocrystalline ribbon wound core, characterized in that: The method comprises the following preparation steps: (1) The amorphous nanocrystalline strip is annealed, crystallized and stress-relieved and wound into a closed magnetic circuit, then immersed in an adhesive resin solution, taken out and heated and cured to obtain a magnetic core; (2) The magnetic core obtained in step (1) is placed in a hard shell, and then the copper busbar is inserted. Finally, the plastic part between the magnetic core and the copper busbar is completed by injection molding to obtain an integrally injection-molded nanocrystalline ribbon wound iron core.

2. The method for preparing a one-piece injection-molded nanocrystalline ribbon wound core according to claim 1, characterized in that: The amorphous nanocrystalline ribbon described in step (1) has a thickness of 10-30 μm and a composition system of FeSiB, FeSiBC, FeNiSiB, FeCuNbSiB, FeNiCuNbSiB, FeCoCuNbSiB, FeCuMoSiB, FeNiCuMoSiB, FeCoCuMoSiB, FeCuPCSiB, FeNiCuPCSiB, FeCoCuPCSiB.

3. The method for preparing a one-piece injection-molded nanocrystalline ribbon wound core according to claim 1, characterized in that: The specific steps of annealing, crystallization and stress relief treatment and winding into a closed magnetic circuit in step (1) are as follows: the amorphous nanocrystalline strip is firstly wound into a closed magnetic circuit, and then isothermal magnetic field annealing, crystallization and stress relief treatment are performed under the conditions of 400~650℃ temperature and magnetic field.

4. The method for preparing a nanocrystalline ribbon wound core formed by integral injection molding according to claim 1, characterized in that: The specific steps of annealing, crystallization, stress relief treatment and winding into a closed magnetic circuit in step (1) are as follows: The amorphous nanocrystalline strip is added into the roll-to-roll annealing device and conveyed by the pressure rollers. At the same time, a linear laser heating device, an electromagnetic induction heating device or a Joule heat treatment device is arranged along the width direction of the strip on one or both sides of the strip. Linear dynamic crystallization annealing and stress relief treatment are performed during the conveying process of the strip, and then the strip is wound into a closed magnetic circuit.

5. The method for preparing a nanocrystalline ribbon wound core formed by integral injection molding according to claim 4, characterized in that: The laser heating device is a laser with a power of 50~2000W. The high-energy laser beam emitted by the laser performs line scanning along the width direction of the strip, and the strip in the area where the laser beam flows out of the beam rapidly undergoes nanocrystallization and stress relief annealing; the electromagnetic induction heating device is a flat induction heating coil with a power of 50~10000W. The strip in the area where the induction heating coil passes rapidly undergoes nanocrystallization and stress relief annealing; the Joule heat treatment device is a pair of carbon brush electrodes arranged on both sides of the strip in the width direction. The carbon brush electrodes are output with a current of 1~200A by a DC power supply, and the area where the current flows completes the rapid nanocrystallization and stress relief annealing of the strip.

6. The method for preparing an integrally injection-molded nanocrystalline ribbon wound core according to claim 1, characterized in that: The closed magnetic circuit in step (1) is annular, rectangular or racetrack-shaped.

7. The method for preparing an integrally injection-molded nanocrystalline ribbon wound core according to claim 1, characterized in that: The adhesive resin glue in step (1) is epoxy resin glue, polyurethane resin glue, polyacrylate resin glue or silicone resin glue; the epoxy resin glue includes an epoxy resin matrix and an epoxy resin curing agent, and the epoxy resin curing agent is one of amino resin, ethylenediamine, m-phenylenediamine, maleic anhydride, and dicyandiamide; the polyacrylate resin glue includes a polyacrylate resin matrix and a polyacrylate curing agent, and the polyacrylate curing agent is one of isocyanate, aziridine, and triacetylacetonate aluminum; the silicone resin glue includes vinyl polysiloxane and hydrogen-containing polysiloxane, or the silicone resin glue includes epoxy polysiloxane and amino polysiloxane.

8. The method for preparing an integrally injection-molded nanocrystalline ribbon wound core according to claim 7, characterized in that: The epoxy polysiloxane is prepared by the following method: The hydrogen-containing silicone oil, allyl glycidyl ether and an organic solvent are mixed evenly, and then a chloroplatinic acid isopropanol solution catalyst is added and heated for reaction to obtain epoxy polysiloxane.

9. The method for preparing an integrally injection-molded nanocrystalline ribbon wound core according to claim 8, characterized in that: The number average molecular weight of the hydrogen-containing silicone oil is 1000-10000, and the hydrogen content is 0.2-1wt.%; the amount of allyl glycidyl ether is 5%-30% of the mass of the hydrogen-containing silicone oil; the organic solvent is one or more of N,N-dimethylformamide, toluene, xylene, ethyl acetate, butyl acetate, n-hexane, n-heptane, acetone, butanone, tetrahydrofuran, and isopropanol; the amount of the organic solvent is 5%-20% of the total mass of the hydrogen-containing silicone oil and allyl glycidyl ether; the temperature of the heating reaction is 70-90°C, and the time is 1-6h.

10. The method for preparing an integrally injection-molded nanocrystalline ribbon wound core according to claim 7, characterized in that: The amino polysiloxane has an amino mass percentage of 0.2% to 2% and a viscosity of 50 to 1000 cps.

11. The method for preparing an integrally injection-molded nanocrystalline ribbon wound core according to claim 1, characterized in that: The temperature of the heating and curing molding in step (1) is 60~220℃.

12. The method for preparing an integrally injection-molded nanocrystalline ribbon wound core according to claim 1, characterized in that: The injection molding temperature in step (2) is 120-360° C. and the pressure is 30-300 MPa; the material of the hard shell is aluminum alloy, iron alloy or plastic.

13. A nanocrystalline ribbon wound core, characterized in that: It is prepared by the method according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Injection-molded reactor and compound used in same

    CN103946935A

  • Insulating enamel and method of making same

    CN106700902A

  • Heat-treatment method for iron-base amorphous alloy strip, magnetic core and mutual inductor

    CN108962583A

  • Nano-crystal magnetic core, nano-crystal inductor and preparation method of nano-crystal magnetic core and nano-crystal inductor

    CN114927303A

  • Nanocrystalline magnetic core and preparation method thereof

    CN117038306A

Cited By

  • Preparation method of nanocrystalline magnetic core

    CN120261157A

  • A method for preparing nanocrystalline magnetic core

    CN120261157B